Assessment of Feeding Acceptance and Injury of Kerman Pistachios, Pistacia vera, by Brown Marmorated Stink Bug (Hemiptera: Pentatomidae). Issue 5 (21st October 2017) - Lara, Jesús R; Kamiyama, Matthew T; Hernandez, Gabriel; Nay, Justin; Hoddle, Mark S
Abstract: In the United States, California (CA) is the primary commercial producer of pistachio nuts, Pistacia vera L. (Anacardiaceae). The brown marmorated stink bug (BMSB), Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), an invasive and polyphagous insect pest from Asia, has established in urban areas in several pistachio-growing counties in CA. Breeding BMSB populations have not been detected in commercial pistachio acreage. However, the detection of BMSB in Kern and Fresno counties, major Kerman pistachio producing areas in CA, underscored key knowledge gaps on BMSB ecology in CA and motivated investigations on the susceptibility of pistachio nuts to BMSB feeding. Laboratory feeding trials conducted in quarantine under permit indicated that adult BMSB stylets can penetrate developing pistachio shells and associated feeding was correlated with kernel necrosis for nuts collected mid to late season (June to August 2016). Feeding damage estimates indicated that higher levels of kernel injury were associated with female BMSB when compared to feeding by male BMSB. These results suggest that there is probable risk of feeding damage to field grown pistachios from BMSB. The implications of this study for BMSB pest management in the CA pistachio system and future research directions are discussed.